Body count : the War on Terror and civilian deaths in Iraq / Lily Hamourtziadou. - Hamourtziadou, Lily (Bristol University Press, 2021)
Lily Hamourtziadou's important analysis of the scale and causes of civilian deaths in Iraq since the US-led coalition's 2003 invasion sheds new light on the War on Terror. From early fighting to the departure and return of troops and the rise of ISIS, she tracks the cost of conflict and constructs an insightful human security approach to war.